Evaluation of magnetic nanoparticle as magneto-motive ultrasound imaging constrast - Arsalani, Saeideh (2018)
Magnetic nanoparticles have been proven as great promising material for biology and medicine applications including protein purification, bacterial detection, drug delivery, hypertherrnia and imaging techniques such as magnetic resonance imaging (MRI), position emission tomography (PET), single photon emission computed tomography (SPECT), optical imaging and magnetic particle imaging and magnetic particle imaging. Recently several researchers have been developing magnetomotive ultrasound imaging (MMUS) as an imaging technique to improve the sensitivity of ultrasound to detect magnetic nanoparticles. In this technique (MMUS), an external magnetic excitation is applied in order to induce a motion within tissue labeled with magnetic nanoparticles and the backscattered ultrasound radio frequency (RF) waves are used to localize and image the magnetically induced motions within tissue. These vibrations, in order of micro meters, are originated from the interaction of the particles with an external oscillating magnetic field. Lately, a type of MMUS, shear-wave dispersion magneto-motive ultrasound (SDMMUS) has been proposed to analyze the mechanical properties of the medium as a remote elastography novel technique. Interaction of the magnetic nanoparticles with an external magnetic field can generate a shear wave within the medium which has been labeled with these nanoparticles. The propagation of this wave provides information about viscoelastic properties of the medium including shear elasticity (µ1) and shear viscosity (µ2). In this method, the Levenberg-Marquardt algorithm, as a nonlinear fitting, was applied to calculate the velocity of shear wave versus excitation frequency in order to estimate viscoelasticity parameters. In this thesis, various tissue mimicking phantoms of gelatin, labeled with different superparamagnetic nanoparticles (Fe3O4) with different magnetization, were evaluated as ultrasound contrast. For each phantom one inclusion was used to generate shear wave dispersion magneto motive ultrasound imaging (SDMMUS). The effect of magnetization (which is directly related to magnetic susceptibility) on SDMMUS experiments were investigated and mechanical properties of the phantoms including shear elasticity and shear viscosity were calculated using generated shear wave. Finally, according to the results the optimized magnetic nanoparticle among those which were used in this thesis was Fe3O4 covered with latex. As it was expected, this optimized nanoparticle was the one with the highest magnetization and the results confirmed the direct relation of magnetization with induced displacement of magnetic nanoparticles